First Record of a Hyalid Species, Protohyale pumila (Crustacea: Amphipoda: Hyalidae), from Korea - Myung-Hwa Shin; Won Kim (Animal Systematics, Evolution and Diversity, 2012)
A hyalid amphipod, Protohyale pumila (Hiwatari and Kajihara, 1981), collected from Jeju Island is reported for the first time in the Korean fauna. The species is characterized by the presence of a short apical spine on the palp article 4 of maxilliped, a distinctly large and blunt cusp on the propodus of male gnathopod 1, and a distal truncate process on the palm of male gnathopod 2. Herein, the present species is described and illustrated. Korean hyalid amphipods now are composed of four species belonging to three genera. Voucher specimens were deposited in the Marine Arthropod Depository Bank of Korea, Seoul National University.